2020
DOI: 10.1002/jcsm.12575
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of myosteatosis in patients with colorectal cancer: a systematic review and meta‐analysis

Abstract: Background Myosteatosis has been reported to be a novel biomarker that could predict survival outcomes in patients with colorectal cancer. However, results have been conflicting. This systematic review and meta-analysis aimed to evaluate the long-term impact of myosteatosis on the survival of these patients. Methods A systematic search of PubMed, Embase, and Cochrane up to 27 November 2019 generated 7022 records. Studies that reported hazard ratio (HR) for overall survival, cancer-specific survival, or disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 50 publications
7
52
1
4
Order By: Relevance
“…SMD is a widely used index for muscle quality and has been shown to be a prognosticator in cancer. 48 Moreover, SMD, but not SMI, was shown to be associated with physical function, 49 indicating that it may be a better marker for severe sarcopenia. However, the results of the present meta‐analysis demonstrated that SMD could not predict the survival in patients treated with ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…SMD is a widely used index for muscle quality and has been shown to be a prognosticator in cancer. 48 Moreover, SMD, but not SMI, was shown to be associated with physical function, 49 indicating that it may be a better marker for severe sarcopenia. However, the results of the present meta‐analysis demonstrated that SMD could not predict the survival in patients treated with ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…Myosteatosis is a negative prognostic factor in cancer and has been associated with worse overall survival in a variety of cancers[ 82 , 83 ]. The pathophysiology of myosteatosis is not well understood, but it is believed that there is a relationship between aging and excess weight that results in ectopic fat deposition in skeletal muscle[ 84 ].…”
Section: Nutritional Status and Postoperative Complicationsmentioning
confidence: 99%
“…There are few recent studies of the effects of the change in body composition that occurs in myosteatosis. Better knowledge of the pathogenesis and validation of diagnostic criteria for myosteatosis are essential for conducting reliable studies to elucidate the impact of this condition on postoperative evolution and to accurately assess preoperative nutritional status[ 83 ].…”
Section: Nutritional Status and Postoperative Complicationsmentioning
confidence: 99%
“…This apparent obesity paradox may be related to the reliance on BMI since this measure does not differentiate lean from fat mass or visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) [17,18], masking the relationship of fat mass with overall survival in men with prostate cancer [19,20]. Furthermore, sarcopenia or the loss of muscle mass has also been considered an important prognostic factor [6,[21][22][23], although its association with overall survival in men with prostate cancer is largely controversial depending on the cancer stage or phase of treatment [16,24,25]. Therefore, it remains to be determined if excess fat mass, reduced levels of muscle mass, or both treatment-related changes in body composition have an impact on overall survival in men with prostate cancer [20].…”
Section: Introductionmentioning
confidence: 99%